دور التسويق الرقمي وأبعاده في تعزيز ادارة علاقات الزبائن في شركات الاتصالات - روستم, كاوه محمد (Sulaimani Journal for Humanities, 2021)
This research was conducted to identify the relationship and impact of digital marketing and its dimensions on customer relationship management in the telecommunications companies. The main research problem is presented through the question: "What is the role of digital marketing and its dimensions in enhancing customer relationship management in the surveyed sample?" The importance of the research appears in analyzing and defining the main variables in the theoretical and field sides. In light of this, the researcher developed the hypothetical outline of the research for the systematic treatment of the problem. The researcher divided the research hypotheses into link hypotheses and impact hypotheses. The research population consisted of employees working at Asiacell and Korek Telecom companies in Sulaymaniyah governorate. The researcher adopted the random sampling technique in distributing the questionnaire that was prepared for this purpose and relied on five-point Likert scale. The research sample included 93 participants in the two aforementioned companies. The researcher applied a descriptive and analytical approach so as through statistical method explain the positive and negative causes that serve the objectives of the current research. The hypotheses were tested using simple and multiple linear regression and the Pearson correlation coefficient relying on SPSS to conduct this analysis. Among the most important conclusions that were reached: it became clear that there is a significant impact of digital marketing and its dimensions as an independent variable on managing customer relations as an dependent variable. This means that any qualitative change in digital marketing of services in telecommunications companies will affect the maintenance of relations with customers. Accordingly, the researcher presented a set of proposals. The most important of which embodied the need to use marketing and technical expertise in relation to studies and research in the field of marketing, especially with regard to the field of technology relationship and the purchasing behavior of customers in the surrounding environment and how to exploit the opportunities in this environment.
Keywords: Digital Marketing; Customer Relationship Management; Asiacell Communications Company; Korek Telecom Company